Efektivitas Pemberian Ekstrak Garlic terhadap Penurunan Tekanan Darah pada Ibu Hamil dengan Hipertensi di UPT Puskesmas Pahandut Kota Palangkaraya - Rizki Muji Lestari; Fitriani Ningsih (Jurnal Surya Medika (JSM), 2021)
Pregnancy is something that every married couple always looks forward to, but over time not all pregnancies go smoothly. Hypertension in pregnancy is one of the complications that often occur in pregnant women. Hypertension in pregnancy is common and is the leading cause of maternal death and has other serious effects during labor. Hypertension in pregnancy occurs in 5% of all pregnancies. Garlic is one type of natural wealth that can reduce blood pressure because garlic has active compounds that are known to affect the availability of ions for the contraction of smooth muscle in blood vessels. This study used a sample of 30 respondents of pregnant women with hypertension who came to the KIA room at the Pahandut Health Center, Palangka Raya City, totaling 30 respondents. In this study, the independent variable was garlic extract intervention, while the dependent variable was blood pressure. In this study, using a Paired Sample T-Test statistical test using a computerized. From the results of the study, it can be seen that the mean difference between the first and second measurements is 8.63 with a standard deviation of 5. This difference is then tested with the paired T-test resulting in a test that is obtained by 0.00, so it can be concluded that there is a significant difference in blood pressure at the first measurement and the second measurement.